Job Crafting and Meaningful Work for Employees at Pt. X In Jakarta - Anugrah, Yohana Dian; Wijono, Sutarto (International Journal of Business Studies, 2025)
In the new normal era, both organizations and employees have had to rapidly adjust to unparalleled difficulties. PT. X, a digital consulting firm that focuses on installing core modules and ensuring safety equipment for mining machines, has faced similar challenges. To maintain a competitive edge, PT. X must prioritize the continuous productivity of its employees while also improving the quality and significance of their jobs. This will help to keep employees motivated and enable them to effectively adjust to any changes in the workplace. This study examined the relationship between job crafting and the experience of meaningful work among employees working at digital consulting firms in Jakarta. The study employed a quantitative approach and included a sample of 55 employees who were selected using saturation sampling techniques. The data was gathered via adapted iterations of the Comprehensive Meaningful Work Scale (CMWS) and Job Crafting Scale (JCS). Pearson's correlation analysis showed a significant positive association between job crafting and meaningful work. This suggests that employees who engage in higher degrees of job crafting tend to perceive their work as more meaningful. The results emphasize the importance of job design in improving the quality of meaningful work experiences. Organizations can cultivate a sense of meaningful work by promoting job-creating behaviors that empower employees to modify their duties and interactions. During periods of transition and uncertainty, it is especially important to have meaningful work, as it can inspire and drive people while also aiding the business in adapting to the new normal.